PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN TRANSFORMASIONAL, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI (PT. TELEKOMUNIKASI INDONESIA WITEL SEMARANG) - Bastiani, Dwi Arini; Rahardjo, Mudji (Diponegoro Journal of Management, 2017)
This research aims to determine the influence of organizational culture, transformational leadership style and job satisfaction towards organizational commitment at PT. Telekomunikasi Indonesia Witel Semarang.The sampling method used on this research is proportional random sampling. Samples were collected from 70 respondents who are employees at PT. Telekomunikasi Indonesia Witel Semarang. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression test and hypothesis test.The result showed that organizational culture, transformational leadership style had no effect on organizational commitment. While job satisfaction is the only variable that has significant influence on organizational commitment.